A New Black Fly Species of the Simulium (Gomphostilbia) duolongum Subgroup (Diptera: Simuliidae) from Vietnam, and Molecular Comparisons with Related Species Using the COI Barcoding Gene - Takaoka, Hiroyuki; Low, Van Lun; Tan, Tiong Kai; Ya'cob, Zubaidah; Sofian-Azirun, Mohd; Chen, Chee Dhang; Lau, Koon Weng; Pham, Xuan Da (Oxford University Press, 2018)
Simulium (Gomphostilbia) yvonneae sp. nov. is described based on adults, pupae, and mature larvae from Vietnam. This new species belongs to the Simulium duolongum subgroup in the S. batoense species-group of the subgenus Gomphostilbia Enderlein. It is distinguished by having a relatively larger number of male upper-eye facets in 16 vertical columns and 16 horizontal rows and a pupal gill with eight filaments arranged as 3+(1+2)+2 from dorsal to ventral, of which two filaments of the ventral pair are 1.8 times as long as the longest filament of the middle and dorsal triplets. Morphological comparisons are made to distinguish this new species from all 22 related species. The genetic distinctiveness of this new species in the S. duolongum subgroup is also presented based on the DNA barcoding COI gene. © The Author(s) 2018. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved.